1997
DOI: 10.1002/(sici)1098-2795(199709)48:1<127::aid-mrd15>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin content, Ca2‐dependent calmodulin binding proteins, and testis growth: Identification of Ca2‐dependent calmodulin binding proteins in primary spermatocytes

Abstract: In contrast with the transient pre-replicative increase in calmodulin (CaM) level observed in proliferative activated cells, postnatal development of rat testis was paralleled by 3 specific rises in CaM. The first one occurred between 5 and 10 days, coincident with the appearance and proliferation start of spermatogonia and Sertoli cells. Meiosis accomplishment and spermatid differentiation were paralleled by 2 additional rises, at 24 and 32 days, respectively. The plateau phase of testis growth was coincident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…Significantly, the regulated pattern of MAP2 mRNA expression in the testis coincides with the progression of the germ cells into their post-mitotic phase of development, and using immunohistochemistry, MAP2 protein was detected in this study in the nucleus of germ cells in the later stages of meiosis and in the nuclei of round spermatids. This pattern correlates with the time at which calmodulin is reported to move from the cytoplasm into the nucleus of germ cells (45,46). Significantly, the latter study identified a number of calmodulin-binding proteins that were nuclear under these conditions, including one of 75 kDa, which was associated with the nuclear matrix of pachytene spermatocytes.…”
Section: Discussionsupporting
confidence: 54%
“…Significantly, the regulated pattern of MAP2 mRNA expression in the testis coincides with the progression of the germ cells into their post-mitotic phase of development, and using immunohistochemistry, MAP2 protein was detected in this study in the nucleus of germ cells in the later stages of meiosis and in the nuclei of round spermatids. This pattern correlates with the time at which calmodulin is reported to move from the cytoplasm into the nucleus of germ cells (45,46). Significantly, the latter study identified a number of calmodulin-binding proteins that were nuclear under these conditions, including one of 75 kDa, which was associated with the nuclear matrix of pachytene spermatocytes.…”
Section: Discussionsupporting
confidence: 54%
“…Hence, components of the importin/Ran GTP-or CaM-dependent pathways may act to regulate nuclear accumulation of SOX9 into Sertoli cells to allow a sufficient amount of SOX9 protein to activate the anti-Mullerian hormone gene, MIS, SF1, and other genes. The subcellular localization and expression of CaM varies during testis development with CaM levels increasing just prior to the proliferation of Sertoli cells and spermatagonia (46,47). The calcium-CaM status of the Sertoli cells could be critical at this time when cells in the XY gonad are being committed as Sertoli cells.…”
Section: Discussionmentioning
confidence: 99%